Managing software projects with team software process (TSP) - Hamid, S. S. (IGI Global, 2013)
Despite the widespread use of sound project management practices and process improvement models over the last several years, the failure of software projects remains a challenge to organisations. As part of the attempt to address software industry challenges, several models, frameworks, and methods have been developed that are intended to improve software processes to produce quality software on time, under budget, and in accordance with previously stipulated functionalities. One of the most widely practised methods is the Team Software Process (TSP). The TSP was designed to provide an operational framework for establishing an effective team environment and guiding engineering teams in their work. This chapter provides an overview of the TSP and its associated structures and processes. It also highlights how the TSP operational framework can assist project manager and software development team to deliver successful projects by controlling and minimizing the most common software failure factors. Comparative analysis between the TSP and conventional project management has also been presented. Additionally, the results of TSP implementation in industrial settings are highlighted with particular reference to scheduling, quality, and productivity. The last section indicates additional advantages of TSP and comments on the future of TSP in the global software development project.